(untitled) (Scientific journal of the Fergana State University, 2025)
The emergence of the first cities in the Fergana Valley, the agricultural culture in the valley was closely related to centralized production. Cities were formed as a process of production and the formation of trade centers in agro-irrigated oases. The processes of the formation of urban centers in oases are considered to be important factors in society. The topography of the ancient cities in the Fergana Valley is fundamentally different from the cities of the early Iron Age. The article studies them in connection with migration processes in the region.